2019
DOI: 10.1016/j.joca.2018.09.010
|View full text |Cite
|
Sign up to set email alerts
|

MiR-15b is a key regulator of proliferation and apoptosis of chondrocytes from patients with condylar hyperplasia by targeting IGF1, IGF1R and BCL2

Abstract: Keywords:MiR-15b Condylar hyperplasia IGF1 IGF1R BCL2 s u m m a r yObjective: This study aimed to explore potential microRNAs (miRNAs), which participate in the pathological process of condylar hyperplasia (CH) through targeting specific proliferation-and apoptosisrelated genes of chondrocytes. Methods: Insulin-like growth factor 1 (IGF1), IGF1 receptor (IGF1R) and B-cell CLL/lymphoma 2 (BCL2) in CH cartilage were detected by real-time polymerase chain reaction (PCR), Western blot, immunohistochemistry and imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…13 Importantly, a recent study shows that miR-15b is a key regulator of proliferation and apoptosis of chondrocytes from patients with condylar hyperplasia by targeting insulin-like growth factor 1 (IGF1), IGF1 receptor (IGF1R) and B-cell CLL/lymphoma 2 (BCL2). 14 Importantly, the present study shows that LINC00662 was decreased in joint tissue of OA, the sponging effect on miR-15b-5p was increased. Then the inhibitory effect of miR-15b-5p on GPR120 was increased, leading to decreased GPR120 and OA.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…13 Importantly, a recent study shows that miR-15b is a key regulator of proliferation and apoptosis of chondrocytes from patients with condylar hyperplasia by targeting insulin-like growth factor 1 (IGF1), IGF1 receptor (IGF1R) and B-cell CLL/lymphoma 2 (BCL2). 14 Importantly, the present study shows that LINC00662 was decreased in joint tissue of OA, the sponging effect on miR-15b-5p was increased. Then the inhibitory effect of miR-15b-5p on GPR120 was increased, leading to decreased GPR120 and OA.…”
Section: Discussionsupporting
confidence: 46%
“…Studies show that miR‐15b‐5p exhibits dual roles by accelerating or blocking tumor progression . Importantly, a recent study shows that miR‐15b is a key regulator of proliferation and apoptosis of chondrocytes from patients with condylar hyperplasia by targeting insulin‐like growth factor 1 (IGF1), IGF1 receptor (IGF1R) and B‐cell CLL/lymphoma 2 (BCL2) …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, ectopic expression of miR-204 triggers spontaneous cartilage loss and OA development, whereas miR-204 inhibition results in concomitant recovery of prostaglandins synthesis and suppression of inflammatory senescence-associated secretory phenotype (SASP) factors in experimental OA [16]. It has been demonstrated that miR-15b regulates chondrocytes proliferation and apoptosis by targeting IGF1, IGF1R, and BCL2 from patients with condylar hyperplasia [17] and knockdown of microRNA-203 alleviates LPS-induced injury by targeting MCL-1 in C28/I2 chondrocytes [18]. Recent in vitro studies have revealed that miR-449a inhibition promotes cartilage regeneration and prevents progression of osteoarthritis [19].…”
Section: Introductionmentioning
confidence: 99%
“…In several studies, BCL2 has been reported to act as a target gene of multiple miRNAs, including miR‐153, miR‐136 and miR‐365 . BCL2 has also been elucidated to be a target gene of miR‐15b in condylar hyperplasia and liver cancer . miR‐15b has been shown to play a role in the development of multidrug resistance in gastric cancer cells, at least in part by modulation of apoptosis via targeting BCL2 .…”
Section: Discussionmentioning
confidence: 99%